Radiation effects on the structure and alteration behavior of an SiO2–Al2O3–B2O3–Na2O glass. (27th October 2022) - Jan, Amreen; Delaye, Jean‐Marc; Kaya, Huseyin; Kim, Seong H.; Mir, Anamul Haq; Charpentier, Thibault; Angeli, Frédéric; Gin, Stephane
Abstract: As borosilicate glasses are used in many countries to immobilize fission products and minor actinides after spent fuel reprocessing before storage in a deep geological repository, assessing that their chemical durability is of paramount importance. Here, pristine and preirradiated (952 MeV, 136Xe) SiO2 –B2 O3 –Al2 O3 –Na2 O glasses with the same molar ratios as in the French SON68 and ISG glasses have been subjected to aqueous corrosion in deionized water and in silica‐saturated solution to measure the initial and longer term alteration rates. Pristine and preirradiated glasses corrode following the same mechanisms, but the preirradiation has a strong impact on the initial dissolution rate (increase by a factor of 5.6), and on the alteration layer depth in silica‐saturated conditions (by two‐ to threefolds). The later result is related to the formation of a more porous, less passivating gel on the preirradiated glass specimen. Using both experimental spectroscopies (NMR, IR, and SFG) and classical molecular dynamics, the radiation effects on the glass structure and water diffusion have been assessed. After preirradiation, the density and the polymerization degree of the glass decrease, whereas the topological disorder increases. In consequence, water diffusion accelerates. These observations allow to correlate the radiation impact on the alteration behavior to the structural changes.